Adenoid cystic carcinoma of the breast: case report - Marinho, Matheus Lavigne; Tafuri, Alexandre; Ramos, Carlos Alberto da Silva; Ladeia, Antônio Alexandre Lisbôa; Azevedo, Luciana de Carvalho (Mastology, 2021)
Adenoid cystic carcinoma (AdCC) of the breast is an uncommon invasive lobular neoplasm whose morphology is similar to the homonymous tumor of salivary glands and with a peculiar behavior toward the “triple-negative” (TN) profile. Tumors belonging to this family do not immunohistochemically express three of the main prognostic biomarkers and tend to show a more aggressive behavior. However, this rare histological pattern of breast cancer is generally associated with good prognosis. In this study, the authors describe the case of a 49-year-old woman diagnosed with this rare malignant tumor and who underwent breast-conserving surgery. Recent studies have aimed to understand the genes, genetic alterations, and etiological aspects related to the still obscure etiopathogenesis of AdCC. Thus, morphological and molecular aspects relevant to AdCC and reported in the literature will be discussed.